2015
DOI: 10.1080/00207543.2015.1041570
|View full text |Cite
|
Sign up to set email alerts
|

The development of a decision support framework for a quantitative risk assessment in multimodal green logistics: an empirical study

Abstract: The objective of this research was to develop a decision support framework (DSF) to assess quantitative risk in multimodal green logistics. This risk assessment is the combination of a number of models, the failure mode and effects analysis, the risk contour plot, the quantitative risk assessment, the analytic hierarchy process and the data envelopment analysis which can support a user to perform risk assessment in various decisions. The contribution of this research is that the risk assessment model can gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 40 publications
(85 reference statements)
0
56
0
1
Order By: Relevance
“…Shankar et al [72] quantified the dynamic uncertainties and intrinsic sustainability risks of freight transport and stated that most of the risks were socially induced rather than financially driven. The risks of multimodal green logistics were analyzed by Kengpol and Tuammee [73]. A system dynamics simulation conducted by Sudarto et al [74] revealed that the economic performance of G&SL is directly affected by freight policy, while environmental performance is indirectly affected.…”
Section: Planning Policy and Management Research Of Gandslmentioning
confidence: 99%
“…Shankar et al [72] quantified the dynamic uncertainties and intrinsic sustainability risks of freight transport and stated that most of the risks were socially induced rather than financially driven. The risks of multimodal green logistics were analyzed by Kengpol and Tuammee [73]. A system dynamics simulation conducted by Sudarto et al [74] revealed that the economic performance of G&SL is directly affected by freight policy, while environmental performance is indirectly affected.…”
Section: Planning Policy and Management Research Of Gandslmentioning
confidence: 99%
“…Kengpol et al [6] presented a DSS to select multimodal routes between Thailand and Vietnam, but did not mention physical characteristics. Kengpol et al [7] and Kengpol and Tuammee [8], who studied the multimodal transportation routing had acknowledged that a few physical route characteristics were classified in the infrastructure and equipment risks: capacity of bridges on the route, tunnels, slope and the width of roads, etc. However, this study adopted comprehensive risk assessment, without consideration of individual physical route characteristics.…”
Section: The Standard Criteria For Physical Road Freight Transportatimentioning
confidence: 99%
“…Kengpol et al [7] established a new conceptual framework for route selection in multimodal transportation. Kengpol and Tuammee [8] introduced a decision support framework (DSF) for a quantitative risk assessment in multimodal green logistics, the DSF integrated quantitative risk assessment, Analytic Hierarchy Process (AHP) and Data Envelopment Analysis (DEA). Sattayaprasert et al [9] represented a method which used the model of Hazardous Material (HazMat) transportation routing with AHP to evaluate risk elements: risk of carriage unit explosion, risk of road accidents, and consequences of an incident.…”
Section: Introductionmentioning
confidence: 99%
“…Fahimnia et al (2015) investigated the impacts of carbon pricing on manufacturing and distribution planning decisions by presenting a trade-off of supply chain models. Kengpol and Tuammee (2016) developed a decision-support framework (DSF) to assess quantitative risk in multimodal green logistics.…”
Section: Introductionmentioning
confidence: 99%